2023
DOI: 10.1186/s12903-023-03552-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial efficacy of different combinations of calcium hydroxide against Enterococcus faecalis

Kavalipurapu Venkata Teja,
Krishnamchari Janani,
Kumar Chandan Srivastava
et al.

Abstract: Background The study aims to compare the synergistic antibacterial efficacy of different combinations of calcium hydroxide as an intracanal medicament against E. faecalis. Material and methods The current study included four hundred extracted human permanent mandibular premolar teeth. After complete chemo-mechanical preparation, the middle third of the root was sectioned using a rotary diamond disc and a total of 400 samples were obtained. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Relying solely on chemical disinfection may be insufficient, underscoring the critical importance of selecting an appropriate intracanal medicament to comprehensively eradicate microorganisms in such cases. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Relying solely on chemical disinfection may be insufficient, underscoring the critical importance of selecting an appropriate intracanal medicament to comprehensively eradicate microorganisms in such cases. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Studies have shown that a significant proportion, ranging from 40% to 60%, of cultivable bacteria remains present in the root canals, even after undergoing irrigation with sodium hypochlorite. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that incorporating CSNPs into a Ca(OH) 2 -based paste has the potential to increase its antibacterial activity and inhibit bacterial recolonization on root canal dentin; meanwhile, the Ca(OH) 2 /EPE paste was not able to maintain its antibacterial efficacy over time [ 175 ]. Teja et al explored the additive effects of various nanoparticles combined with Ca(OH) 2 on E. faecalis biofilms, concluding that AgNP incorporation into Ca(OH) 2 showcased superior efficacy [ 176 ]. Accumulating studies have also demonstrated that AgNPs mixed with Ca(OH) 2 present more pronounced antibiofilm effects against E. faecalis , C. albicans , F. nucleatum , and even multispecies biofilms compared to Ca(OH) 2 [ 177 , 178 , 179 , 180 ].…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%